Effects of biochar in combination with varied N inputs on grain yield, N uptake, NH3 volatilization, and N2O emission in paddy soil - Yi, Zhenghua; Jeyakumar, Paramsothy; Yin, Chengcheng; Sun, Haijun (Frontiers in Microbiology, 2023)
Biochar application can improve crop yield, reduce ammonia (NH3) volatilization and nitrous oxide (N2O) emission from farmland. We here conducted a pot experiment to compare the effects of biochar application on rice yield, nitrogen (N) uptake, NH3 and N2O losses in paddy soil with low, medium, and high N inputs at 160 kg/ha, 200 kg/hm2 and 240 kg/ha, respectively. The results showed that: (1) Biochar significantly increased the rice grain yield at medium (200 kg/ha) and high (240 kg/ha) N inputs by 56.4% and 70.5%, respectively. The way to increase yield was to increase the rice N uptake, rice panicle number per pot and thousand grain weight by 78.5-96.5%, 6-16% and 4.4-6.1%, respectively; (2) Under low (160 kg/ha) N input, adding biochar effectively reduced the NH3 volatilization by 31.6% in rice season. The decreases of pH value and NH4+-N content in surface water, and the increases of the abundance of NH4+-N oxidizing archaea and bacteria (AOA and AOB) communities contributed to the reduction of NH3 volatilization following the biochar application; (3) Under same N input levels, the totalN2O emission in rice season decreased by 43.3-73.9% after biochar addition. The decreases of nirK and nirS gene abundances but the increases of nosZ gene abundance are the main mechanisms for biochar application to reduce N2O emissions. Based on the results of the current study, adding biochar at medium (200 kg/ha) N level (N200+BC) is the best treatment to synchronically reduce NH3 and N2O losses, improve grain yield, and reduce fertilizer application in rice production system.